The Transformative Role of Christian Public Theology in the Context of Multiculturalism, Globalisation, and Popular Culture - Marde Christian Stenly Mawikere; Sudiria Hura (Philosophy Global: International Journal of Christian and Catholic Philosophy, 2025)
This study investigates the role of Christian public theology in advancing social transformation, with particular emphasis on social justice, intercommunal solidarity, and sustainable development. Employing a qualitative methodology grounded in critical literature review, the research explores the engagement of public theology with the prevailing contexts of multiculturalism, globalisation, and popular culture. The findings reveal that public theology functions as a vital bridge between Christian faith—which proclaims Jesus Christ as the sole Saviour and restorer of creation—and tangible societal change within both private and public spheres. The study underscores the distinctive character of Christian public theology as an authentic and contextual agent of transformation, upholding the integrity of the Gospel message.